Left Juxtaposition of the Right Atrial Appendage: Pitfalls in Diagnosis - Kanya Singhapakdi; Wesam Sourour; Thomas R. Kimball (Case Reports in Cardiology, 2023)
Several congenital anomalies of the right atrial appendage (RAA) have been described including aneurysm, herniation (in association with a pericardial defect), and left juxtaposition. The left juxtaposition of the RAA (LJRAA), first described by Birmingham in 1893 and subsequently introduced by Dixon in 1954, is usually associated with complex cardiac malformations such as obstruction of the left ventricular outflow tract. In this case report, we will describe an unusual variant of LJRAA in the absence of any other cardiac defects, which was initially misinterpreted as an aortic dissection. The correct diagnosis was made after careful reinterpretation and the use of multiple imaging modalities as highlighted.